PSYCHOLOGICAL WELL-BEING OF THE ELDERLY IN THE TRESNA WERDA SOCIAL ASSOCIATION IN BENGKULU - Helmiyanti Anugerah Siregar; Ishak Fadlurrohim; Indria Agustina (Universitas Negeri Medan, 2025)
This study examines the psychological well-being of elderly residents at the Tresna Werdha Social Institution (PSTW) Bengkulu using six-dimensional framework: self-acceptance, positive relations, autonomy, environmental mastery, purpose in life, and personal growth. Employing a descriptive qualitative design, the research involved observations and in-depth interviews with eight elderly participants selected through purposive sampling. The findings show that the overall psychological well-being of the residents is relatively good, although it varies according to individual physical conditions, social experiences, and personal histories. In terms of self-acceptance, the elderly are generally able to embrace aging-related changes and reinterpret past experiences with gratitude. Most participants maintain positive relationships, supported by warm interactions with peers and staff, despite limited contact with family members. The dimension of autonomy appears stable, as residents can make daily decisions and participate in preferred activities, even though institutional rules sometimes restrict their freedom. Environmental mastery is reflected in their ability to adapt to the physical and social environment, participate in routine programs, and maintain personal spaces. The participants also retain meaningful life purposes, expressed through spiritual aspirations, hopes for health, and desires to reconnect with family. Personal growth remains evident as many continue learning, developing patience, and engaging in new activities that strengthen emotional and spiritual maturity. Despite these strengths, several challenges—such as declining health, loneliness, rigid regulations, and limited facilities still hinder optimal well-being. The study highlights the need for enhanced supportive services and more varied activities to further strengthen the psychological well-being of institutionalized elderly individuals. Key words: psychological well-being, elderly, social institution